1994
DOI: 10.1159/000109543
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Metallothionein in the Mammalian Central Nervous System

Abstract: This review concerns the immunohistochemical localization of metallothionein (MT), a metal-binding protein, in the mammalian central nervous system (CNS). Expression of MT in the mammalian CNS is abundant. In the mouse brain, MT expression is found in some glial cells, whereas in the adult rat brain immunoreactivity varies from no expression at all to abundant reactivity throughout the whole brain. In primates and humans, MT expression is mainly found in astrocytes. Thus, MT expression in the mammalian CNS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It is proposed that increased LPO might result in tissue injuries which release cytokines from tissues, and these cytokines can induce MT synthesis (Sato and Bremner, 1993;Shibuya et al, 1995). Recent studies suggest that because MT is present in astrocytes in the central nervous system (Blaauwgeers et al, 1994;Carrasco et al, 1998;Nishimura et al, 1992), astrocytes may pla$ an important role in protecting against oxidative stress (kschner, 1997, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that increased LPO might result in tissue injuries which release cytokines from tissues, and these cytokines can induce MT synthesis (Sato and Bremner, 1993;Shibuya et al, 1995). Recent studies suggest that because MT is present in astrocytes in the central nervous system (Blaauwgeers et al, 1994;Carrasco et al, 1998;Nishimura et al, 1992), astrocytes may pla$ an important role in protecting against oxidative stress (kschner, 1997, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The main source of MTs in the brain are astrocytes, although this protein was also found in the epithelium of the choroid plexus of the nerves, endothelium, and meningeal cells. Data with respect to the amount of MTs in neurons are ambiguous, although it was reported that the MT-І+ІІ complex provides the defense of neurons under culture conditions [21,22].…”
Section: Classification Of Metallothioneinsmentioning
confidence: 99%
“…The statement "Detoxication with respect to heavy metals (Cd, Hg, Ag, Au, and Pt), which is mediated by the functioning of hematoencephalic and hematoliquor barriers is the main function of MTs" is at present believed to be well established [11,22].…”
Section: Functions Of Mts In the Cnsmentioning
confidence: 99%
“…2002). In the CNS, the MT‐I and II subtypes are mainly expressed in astrocytes and microglia (Blaauwgeers et al. 1994; Hidalgo et al.…”
mentioning
confidence: 99%
“…Metallothioneins (MTs) are low molecular weight (6-7 kDa), cysteine-rich (30% of the amino acid contents), and ubiquitous stress proteins (Coyle et al 2002). In the CNS, the MT-I and II subtypes are mainly expressed in astrocytes and microglia (Blaauwgeers et al 1994;Hidalgo et al 2001), while the MT-III subtype is predominantly expressed in neuronal cells (Masters et al 1994). The MT-IV subtype has been found in stratified epithelia .…”
mentioning
confidence: 99%